Development and Validation of Questionnaires to Assess Workplace Violence Risk Factors (QAWRF): A Tripartite Perspective of Worksite-Specific Determinants in Healthcare Settings - Mohd Hatta FH; Samsudin EZ; Aimran N; Ismail Z (Dove Medical Press, 2023)
Faizul Haris Mohd Hatta,1 Ely Zarina Samsudin,1 Nazim Aimran,2 Zaliha Ismail1 1Department of Public Health Medicine, Faculty of Medicine, Universiti Teknologi MARA, Selangor, Malaysia; 2College of Computing, Informatics, and Media, Universiti Teknologi MARA, Shah Alam, Selangor, MalaysiaCorrespondence: Ely Zarina Samsudin, Email elyzarina07@yahoo.comIntroduction: Workplace violence (WPV) incidences are prevalent in healthcare, and existing WPV interventions have only moderate evidence for effectiveness. This study aimed to develop and validate an instrument to assess worksite-specific WPV risk factors in healthcare settings based on a tripartite perspective of key stakeholders to facilitate improved interventions.Methods: Three questionnaires were developed to get the responses from healthcare administrators, workers, and clients, representing the three components of Questionnaires to Assess Workplace Violence Risk Factors (QAWRF). The domains of the questionnaires were developed based on The Chappell and Di Martino's Interactive Model of Workplace Violence, and the items were generated from 28 studies identified from a systematic review of the literature. Six experts, 36 raters, and 90 respondents were recruited to assess the content validity, face validity, and usability and reliability of the QAWRF respectively. Item and Scale Level Content Validity Index, Item and Scale Level Face Validity Index, and Cronbach's alpha values were determined for QAWRF-administrator, QAWRF-worker, and QAWRF-client.Results: The psychometric indices for QAWRF are satisfactory.Conclusion: QAWRF holds good content validity, face validity, and reliability, and findings from QAWRF can contribute towards worksite-specific interventions that are expected to be resource efficient and more effective than general WPV interventions.Keywords: workplace violence, healthcare, questionnaire, instrument, tool, risk assessment, risk factors